Struktur Kepemilikan dan Audit Report Lag Pada Industri Perbankan di Asia Tenggara - Ramadhani, Adhi Fitra; Supriyati, Supriyati (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2021)
This study aims to examine the effect of ownership structure on audit report lag in the banking industry in Southeast Asia. The banking industry has different characteristics and operational mechanisms from other industries so that the role of ownership and external auditors is important for the banking industry. 2020 is the year the ASEAN Economic Community (AEC) was implemented in Southeast Asian countries. Industry competition, especially the banking industry between countries, is getting tighter. Therefore, the banking industry is increasingly expanding its network, operational efficiency, increasing the role of resources including investors in the supervisory function in order to be able to compete globally. Ownership structure is important in determining company policy. The data obtained from purposive sampling were 266 sample data for the 2017- 2019 research period. Hypothesis testing uses regression testing and the test results show that only foreign ownership has a significant effect on the audit report lag. On the other hand, managerial ownership, institutional ownership and public ownership have no significant effect on the audit report lag.